Le "fardeau" de la dette publique suisse: Eclairages des recherches scientifiques et pistes pour le futur - Cédric Tille (Graduate Institute of International and Development Studies, 2019)
– The Swiss Federal government finances are in an excellent shape: debt is small (and decreasing), and carries a low interest rate. This paper reviews the prospects for the Swiss finances drawing on the recent literature. We argue that the current policy of running surpluses and paying down the debt is inefficient, and propose three alternatives. First, as the interest rate on the debt is much lower than the GDP growth rate - a pattern that is not unusual - Switzerland could stabilize the debt to GDP ratio and run a primary deficit of abut CHF 2.6 billion (0.37% of GDP). Second, the low cost of debt implies that investments in education and infrastructure are more attractive than in the past. Third, Switzerland could use its implicit asset (the trust of investors) and set up a sovereign wealth fund financed by government debt. We estimate that a fund amounting to 10% of GDP could generate an annual revenue between CHF 0.7 to 2 billion (0.1% to 0.3% of GDP), though these estimates could be refined further.
Keywords: E62; F3; H6; 330; public debt; low interest rates; sovereign wealth fund; Switzerland